Derrida's "aporia of responsibility" in José Rizal's El Filibusterismo. Issue 3 (1st October 2020) - Claudio, Lisandro E.
Abstract: This article examines themes of revolution, responsibility, and colonial suffering in José Rizal's El Filibusterismo . The second and more confounding of Rizal's two novels, El Filibusterismo is vague about the conditions necessary for anti-colonial revolution. The article argues that this vagueness was deliberate and that it constituted an invitation to a collective reflection on revolutionary responsibility. Using Derrida's concept of the "aporia of responsibility, " it shows that Rizal's novel negotiates the tension between individual accountability and collective action. In conjuring a collective impasse, Rizal left a space for the democratic nationalism that he envisioned for the Philippines.